Features of the ultrastructural organization of the aortic wall (experimental study) - Tsytovskyi , M.N.; Dudok , O.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Relevance. The full-scale Russian-Ukrainian war has caused severe medical consequences, intensifying the need for comprehensive awareness within Ukraine and the global community regarding the scale of these challenges and pathways to overcome them, including scientific approaches. Vascular pathologies commonly encountered in daily medical practice, stemming from injuries and infectious diseases, pose a serious threat to patients' lives. A crucial prerequisite for effective diagnosis and treatment of vascular diseases is a thorough understanding of normal vascular anatomy. Objective. To study the features of the ultrastructural organization of the wall of the normal white rat aorta. Methods. The study material consisted of sexually mature male white rats (n=10), weighing 160-200 g. To achieve the stated objective and study the ultra-morphology of the normal rat aorta wall, the method of electron microscopy was used. Animals were euthanized by overdose of ether anesthesia, and material was collected. Ultrastructural examination was performed using a generally accepted methodology. Biopsies of the ascending aorta, aortic arch, and descending aorta served as the material for the study. Results. The conducted research allowed us to establish the ultrastructural morphological features of the white rat aorta wall structure and perform its comparative anatomical analysis with the human aorta. Conclusion. Despite the existence of numerous comparative studies dedicated to the normal anatomy of the aorta, the results of our research will help to systematize and supplement existing scientific information for further investigations by morphologists and clinicians regarding the microanatomy of the aorta, from the perspective of developing new methods for the diagnosis, prevention, and treatment of vascular pathologies.